2000
DOI: 10.1001/archpedi.154.11.1085
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Hepatitis B Vaccination

Abstract: Objective: To compare the completion rate of hepatitis B vaccination among adolescents who receive primary care at 2 comprehensive high school-based health centers (SBHCs) and a hospital-based adolescent health center (AHC) to assess predictors for successful immunization. Methods: A retrospective chart review of patients seen for comprehensive history and physical examinations from September 1997 to March 1998 at 2 SBHCs and an AHC was conducted to determine the immunization status for hepatitis B. One SBHC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…34,5052 A study in Denver, Colorado, comparing SBHC users with community clinic users, aged between 14 to 17 years, found that SBHC users were more likely to have received an influenza vaccine (45% vs 18%), a tetanus booster (33% vs 21%), and a hepatitis B vaccine (46% vs 20%). 34 The use of recall notification systems to remind students of necessary vaccines is highly prevalent among SBHCs, which may contribute to high immunization rates.…”
Section: Sbhcs and Health And Social Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…34,5052 A study in Denver, Colorado, comparing SBHC users with community clinic users, aged between 14 to 17 years, found that SBHC users were more likely to have received an influenza vaccine (45% vs 18%), a tetanus booster (33% vs 21%), and a hepatitis B vaccine (46% vs 20%). 34 The use of recall notification systems to remind students of necessary vaccines is highly prevalent among SBHCs, which may contribute to high immunization rates.…”
Section: Sbhcs and Health And Social Outcomesmentioning
confidence: 99%
“…34 The use of recall notification systems to remind students of necessary vaccines is highly prevalent among SBHCs, which may contribute to high immunization rates. 50,52 In an analysis of hepatitis B vaccination completion rates among adolescents (aged 13–19 years) at 3 sites in New York City, rates were significantly higher among teenagers from an SBHC where loudspeaker announcements were made to advertise the vaccine (76% vs a hospital-based adolescent health center, 24%). 52 Also, nearly all SBHCs participate in the Vaccines for Children program, which allows them to provide vaccines to publicly insured or uninsured youth—a group at high risk for low immunization rates.…”
Section: Sbhcs and Health And Social Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,5 Antibody response to vaccination in healthy adolescents has generally been reported to be excellent, 6,7,8 but observational data from the “Reaching for Excellence in Adolescent Care and Health” (REACH) longitudinal cohort of HIV-infected and HIV-uninfected at-risk youth demonstrated only a 70% vaccine response rate in an HIV-uninfected older adolescent population. 9 There were several limitations to the REACH hepatitis B study design including small sample size, retrospective reporting of immunization status, and site-to-site variability in vaccine product used.…”
Section: Introductionmentioning
confidence: 99%